1,2-Diphenyl-2-[(1-phenylethyl)amino]ethanol - Hou, Qing-Gao (International Union of Crystallography, 2012)
In the molecule of the title compound, C(22)H(23)NO, there are two chiral atoms (R* for the C atom attached to the OH group and S* for the C atom attached to the phenyl ring). In the crystal, neighbouring molecules are connected into a chain along the b axis by N—H⋯O hydrogen bonds.